2022
DOI: 10.3390/jcm11113045
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Management of Fistulizing Crohn’s Disease: Evidence beyond Randomized Clinical Trials

Abstract: Fistulizing Crohn’s disease (FCD) remains the most challenging aspect of treating patients with CD. FCD can occur in up to 30% of patients with CD and may lead to significant disability and impaired quality of life. The optimal treatment strategies for FCD require a multidisciplinary approach, including a combined medical and surgical approach. The therapeutic options for FCD are limited due to sparse evidence from randomized clinical trials (RCTs). The current recommendations are mainly based on post hoc anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 157 publications
0
8
0
1
Order By: Relevance
“…The study demonstrated comparable success rates between the two groups, with non-cutting seton showing a lower risk of fecal incontinence. These findings suggested that non-cutting seton techniques can be an effective treatment option for high anal fistulas while mitigating the risk of adverse functional outcomes [ 8 ]. This study aims to evaluate the outcomes of surgical interventions using the cutting seton technique in managing high anal fistulas at a hospital in Al-Madinah.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated comparable success rates between the two groups, with non-cutting seton showing a lower risk of fecal incontinence. These findings suggested that non-cutting seton techniques can be an effective treatment option for high anal fistulas while mitigating the risk of adverse functional outcomes [ 8 ]. This study aims to evaluate the outcomes of surgical interventions using the cutting seton technique in managing high anal fistulas at a hospital in Al-Madinah.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CD often have aggressive fistulizing perianal phenotypes that result in higher rates of surgery, hospitalizations and corticosteroid dependence as compared with the general population [ 6 ]. Unfortunately, there is a lack of convincing data on fistulizing CD; medical and surgical approaches can vary widely in clinical practice [ 7 , 8 , 9 ]. An aggressive approach to complex anal fistulas involving the sphincters may increase the risk of fecal incontinence; these fistulae often persist or recur if primary tracts and secondary extensions are not fully drained [ 9–11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, seton treatment alone is associated with a fistula recurrence rate of up to 47%. In CD patients who have undergone fistulotomies after failure of medical management, fecal incontinence is reported in ~60% of patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab can be used early under the premise of infection control, and it is best to maintain long-term treatment, but it is not recommended to use it together with steroids. According to a meta-analysis of 15 observational studies [18] , the risk of serious infection increased with the combination of anti TNF and corticosteroids (in four cohorts; RR, 1.64; 95 % CI, 1.33–2.03).…”
Section: Discussionmentioning
confidence: 99%